Hydrogen evolution from water using CdS as photosensitizer - Tatiana Oncescu; M. Contineanu; Lucia Meahcov (International Journal of Photoenergy)
Colloidal chemical approaches are increasingly utilised for the preparation and stabilization of semiconductor nanoparticles.